Consensus on the therapeutic management of atopic dermatitis - Brazilian Society of Dermatology - Valeria Aoki; Daniel Lorenzini; Raquel Leão Orfali; Mariana Colombini Zaniboni; Zilda Najjar Prado de Oliveira; Maria Cecília Rivitti-Machado; Roberto Takaoka; Magda Blessmann Weber; Tania Cestari; Bernardo Gontijo; Andrea Machado Coelho Ramos; Claudia Marcia de Resende Silva; et al. (Sociedade Brasileira de Dermatologia, 2019)
Abstract: BACKGROUND: Atopic dermatitis is a highly prevalent inflammatory and pruritic dermatosis with a multifactorial etiology, which includes skin barrier defects, immune dysfunction, and microbiome alterations. Atopic dermatitis is mediated by genetic, environmental, and psychological factors and requires therapeutic management that covers all the aspects of its complex pathogenesis. OBJECTIVES: The aim of this article is to present the experience, opinions, and recommendations of Brazilian dermatology experts regarding the therapeutic management of atopic dermatitis. METHODS: Eighteen experts from 10 university hospitals with experience in atopic dermatitis were appointed by the Brazilian Society of Dermatology to organize a consensus on the therapeutic management of atopic dermatitis. The 18 experts answered an online questionnaire with 14 questions related to the treatment of atopic dermatitis. Afterwards, they analyzed the recent international guidelines on atopic dermatitis of the American Academy of Dermatology, published in 2014, and of the European Academy of Dermatology and Venereology, published in 2018. Consensus was defined as approval by at least 70% of the panel. RESULTS/CONCLUSION: The experts stated that the therapeutic management of atopic dermatitis is based on skin hydration, topical anti-inflammatory agents, avoidance of triggering factors, and educational programs. Systemic therapy, based on immunosuppressive agents, is only indicated for severe refractory disease and after failure of topical therapy. Early detection and treatment of secondary bacterial and viral infections is mandatory, and hospitalization may be needed to control atopic dermatitis flares. Novel target-oriented drugs such as immunobiologicals are invaluable therapeutic agents for atopic dermatitis.